Progranulin attenuates liver fibrosis by downregulating the inflammatory response - Yoo, Wonbeak; Lee, Jaemin; Noh, Kyung Hee; Lee, Sangmin; Jung, Dana; Kabir, Mohammad Humayun; Parka, Dongmin; Lee, Cheolju; Kwon, Ki-Sun; Kim, Ji-Su; Kim, Seokho (NATURE PUBLISHING GROUP, 2019)
Progranulin (PGRN) is a cysteine-rich secreted protein expressed in endothelial cells, immune cells, neurons, and adipocytes. It was first identified for its growth factor-like properties, being implicated in tissue remodeling, development, inflammation, and protein homeostasis. However, these findings are controversial, and the role of PGRN in liver disease remains unknown. In the current study, we examined the effect of PGRN in two different models of chronic liver disease, methionine-choline-deficient diet (MCD)-induced non-alcoholic steatohepatitis (NASH) and carbon tetrachloride (CCl4)-induced liver fibrosis. To induce long-term expression of PGRN, PGRN-expressing adenovirus was delivered via injection into the tibialis anterior. In the CCl4-induced fibrosis model, PGRN showed protective effects against hepatic injury, inflammation, and fibrosis via inhibition of nuclear transcription factor kappa B (NF-kappa B) phosphorylation. PGRN also decreased lipid accumulation and inhibited pro-inflammatory cytokine production and fibrosis in the MCD-induced NASH model. In vitro treatment of primary macrophages and Raw 264.7 cells with conditioned media from hepatocytes pre-treated with PGRN prior to stimulation with tumor necrosis factor (TNE)-alpha or palmitate decreased their expression of pro-inflammatory genes. Furthermore, PGRN suppressed inflammatory and fibrotic gene expression in a cell culture model of hepatocyte injury and primary stellate cell activation. These observations increase our understanding of the role of PGRN in liver injury and suggest PGRN delivery as a potential therapeutic strategy in chronic inflammatory liver disease.
Keywords: GRANULIN-EPITHELIN PRECURSOR; KAPPA-B; INSULIN SENSITIVITY; THERAPEUTIC TARGET; SERUM PROGRANULIN; GROWTH-FACTOR; EXPRESSION; PGRN; ACTIVATION; PROTECTS